Design and Analysis of an Energy-Saving Distributed MAC Mechanism for Wireless Body Sensor Networks. (22nd August 2010) - Otal, Begonya; Alonso, Luis; Verikoukis, Christos
Abstract : The fact that the IEEE 802.15.4 MAC does not fully satisfy the strict wireless body sensor network (BSN) requirements in healthcare systems highlights the need for the design and analysis of new scalable MAC solutions, which guarantee low power consumption to all specific sorts of body sensors and traffic loads. While taking the challenging healthcare requirements into account, this paper aims for the study of energy consumption in BSN scenarios. For that purpose, the IEEE 802.15.4 MAC limitations are first examined, and other potential MAC layer alternatives are further explored. Our intent is to introduce energy-aware radio activation polices into a high-performance distributed queuing medium access control (DQ-MAC) protocol and evaluate its energy-saving achievements, as a function of the network load and the packet length. To do so, a fundamental energy-efficiency theoretical analysis for DQ-MAC protocols is hereby for the first time provided. By means of computer simulations, its performance is validated using IEEE 802.15.4 MAC system parameters.